New Molecular Markers for Prostate Cancer Diagnosis - Amiri, Mahan; Asadi Samani, Leila; Kashi, Amir Hossein; Khadem, Nazanin; Ziaee, Seyed Amir Mohsen; Mowla, Seyed javad (Urology Journal, 2024)
Purpose: Prostate cancer (PCa) is the second most commonly diagnosed cancer and the sixth leading cause of cancer death among men worldwide. Biomarkers are an important tool in the early detection of PCa. Prostate-specific antigen (PSA) is one of the oldest biomarkers for the early detection of PCa. Digital rectal exam (DRE) is another screening test for PCa detection, which is considered as an irritating experience for patients. Biopsy is still the most reliable method for PCa diagnosis; however, patients are prone to complications. Therefore, developing non-invasive and accurate methods for PCa screening seems urgent to avoid unnecessary biopsies. There has been remarkable development in PCa molecular biomarkers discovery, largely through progress in omics technologies. Due to the many benefits of liquid biopsies, a significant set of PCa diagnostic kits have been developed using urine samples. Despite the unique benefits of these kits, there are still many challenges to their widespread use in clinics. Here, we have reviewed the latest developments of PCa biomarkers in liquid biopsies. Methods: Literature on biomarkers for diagnosis of PCa was reviewed during the past two decades. Results: PSA, PHI, PCA3, and 4K score are among the commonly used markers for PCa diagnosis which have been used over a long-moderate length of time with multiple studies on their performance. We performed a review of their performance. Newer markers are among RNA and DNA markers. Multiple non-coding RNAs (mi-RNAs) were reviewed and their performance on Pca diagnosis was reviewed. Long noncoding RNAs (Lnc RNAs) including PlncRNA-1, HOTAIR, SchLAP-1, MALAT1, MEG3, and PRCAT17.3 were summarized. mRNA markers including TMPRSS2:ERG, and HOXC6 were presented. DNA-based markers including PTEN, HOXB13, and BRCA2 were reviewed. Finally, the use of CircRNAs was reviewed for PCa diagnosis. Conclusion: Many reviewed RNA-based biomarkers have promising results in the diagnosis of PCa.